Simulation of crop-weed competition : Models and their applications - Weaver, S.E. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
Competition between crops and weeds is a complex phenomenon. Comprehensive, process-oriented simulation models which treat competition in a mechanistic rather than an empirical fashion, can offer insight into relationships among competition, crop and weed density, relative time of emergence, various morphological and physiological traits, and resource levels. They can also be used for prediction as part of a Systems approach to weed management. This paper reviews the features of a number of recent simulation models of crop-weed competition, the species for which they have been parameterized, and their applications. To date, these models have been used primarily to predict crop yield losses due to weed competition. Their ability to simulate weed seed production in response to the environment has not been exploited. The next step is to link simulation models of crop-weed competition to weed population dynamics models, in order to improve our ability to predict the effect of various weed management strategies over time. Advantages and drawbacks of a modeling approach to weed management problems are discussed.